2011 Review of the Standards and Codes Initiative. (Policy Papers; Policy Paper, 2011)
The Standards and Codes Initiative ('Initiative') has been identified as one of several building blocks for the overhaul of the global financial architecture after the Asian crisis in the late 1990s. Twelve policy areas were selected as key for sound financial systems and a framework for Reports on the Observance of Standard and Codes (ROSCs) was established and has been implemented by the Bank and the Fund for about a decade. Since the Initiative's inception, a majority of member countries have had one or more ROSCs, although-in part due to the voluntary nature of ROSCs-the coverage is not fully complete. After peaking in 2003, the annual number of ROSCs completed has declined considerably. In particular, the number of fiscal transparency and data ROSCs has dropped, reflecting the downsizing of the Fund, and changes in departmental priorities. The reduction in financial sector ROSCs-generally done as a part of the Financial Sector Assessment Program (FSAP)-has been less, although fewer ROSCs have been done per FSAP. Revisions to the standards to incorporate the lessons from the crisis, the initiatives of the Financial Stability Board (FSB), and changes to financial surveillance are likely to have important implications for the future of the Initiative. In particular, the commitment by FSB members to undergo FSAPs every 5 years and the FSB's framework to enhance adherence to international financial standards are likely to boost demand for financial sector ROSCs. These resource pressures impose a greater burden on the prioritization process, and strategic decisions will have to be made to augment resources for the Initiative or on where the resource cuts could come from in order to maintain adequate coverage of non-G20 countries.